(3JMOjO GdbhGYO GdbGfhfjI GdhGLHI GdJWHjb Ydi YbhO GdhSWGA GdJLGQjjf PGJ GdWGHY GdOhdi (B/ s - (3aDGO eMeO eMeO GdYOjfis; (3YfGjJ YHOGdMejO KGHJs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LdeYI GdbGgQI ,s, 2012)
(3JYfi gPg GdQSGdI HJbOje JMdjd eaUd hMd Objb deTcdI JOGNd eLGdGJ GfWHGb GdbhGfjf GdehVhYjI ajeG jJYdb HGdYdGbGJ PGJ GdWGHY GdOhdi GdJi jchf ajgG dTNU eG jSei GdhSjW (B( (3hgPG GdeUWdM jTed Gdhcjd GdJLGQi (B: (3GdSeSGQ (B: (3Gdhcjd HGdYehdI (B: (3hGdeeKd GdJLGQi GdJGHY(B) (3SdWI GdJUQa Ch GOYGA GdJUQa dMSGH TNU BNQ jSei GdCUjd ai GdJYGed eY GdWQa GdKGdK s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi GdYGe hGdNGU (B2012s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B399-425s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOhdjs; (3GdbGfhf GdhGLH GdJWHjb s; (3JfGRY bhGfjf s; (3YbhO GdhSWGA GdJLGQjjf s; (3bGfhf GdJLGQI GdCeejs; (3JWHjb GdbGVj GdhWfj s; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs